Intervensi Keperawatan Dalam Mengatasi Mual Muntah Pasien Kanker Pasca Dilakukan Radioterapi Dan Kemoterapi - Isnaini, Barkah; Novieastari, Enie; Hargiana, Giur; Allenidekania, Allenidekania (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to identify interventions that can be used in managing symptoms of post-chemotherapy nausea and vomiting in cancer patients. The method used was a systematic review by searching five databases including Google Scholar, Portal Garuda, Moraref, and Demension regarding what interventions can be done in dealing with nausea and vomiting conditions in cancer patients, with a publication range from 2000 to 2024. 7131 articles were obtained at the beginning of the data search, after filtering with the PRISMA 2020 method, the final result was 8 articles to be analysed using the Joanna Briggs Institute (JBI) checklist. Seven of these articles used intervention studies. The results of the study showed that there are several interventions that can be carried out. One of the most frequently used interventions is acupressure intervention and the use of aromatherapy in overcoming nausea and vomiting of cancer patients after chemotherapy. It is expected that nurses who work in the chemotherapy room can apply this intervention to patients who experience post-chemotherapy nausea and vomiting.